Reliability and validity of the Chinese (Queen Mary Hospital, Hong Kong version) of the Disabilities of the Arm, Shoulder and Hand on patients with upper extremity musculoskeletal disorders in Hong Kong - Rebecca K.Y. Chan; Y.C. Leung; Frankie K.L. Leung; Christian X.S. Fang; Amy K.P. Cheung; Tony K.C. Lau; Jo Kamen K.M. Fung (SAGE Publishing, 2019)
Objective This study aimed to translate, culturally adopt and validate a Chinese version of the Disabilities of the Arm, Shoulder and Hand (DASH) for use in patients with upper extremity musculoskeletal diseases in Hong Kong. Methods We followed a standard five-stage process: forward translation, synthesis, backward translation, expert panel review and field-testing to achieve linguistic and conceptual equivalence. The version was officially known as Chinese (Queen Mary Hospital, Hong Kong version) DASH. (Chinese QMH,HK version DASH) ( http://www.dash.iwh.on.ca/sites/dash/public/translations/DASH_Chinese_HK_2013.pdf ). Results Its internal consistency was then evaluated with 138 participants suffering from upper extremity musculoskeletal conditions. The results were high in DASH-Disability/Symptom module (DASH-DS) (Cronbach alpha 0.97), DASH-Work module (DASH-W) (Cronbach alpha 0.97) and DASH-Sports / Performing Arts module (DASH-SM) (Cronbach alpha 0.99). The test-retest reliability was evaluated with a subgroup of participants who had completed the Chinese (QMH,HK version) DASH on two occasions, with a median interval of 6.5 days. The results were excellent among DASH-DS Intraclass Correlation Coefficient (ICC) = 0.98 and DASH-W (ICC = 0.90). Good test-retest reliability was found in DASH-SM (ICC = 0.89). Construct validity of DASH-DS showed good correlation with the sub-domains of physical functioning (r = −.564) and social functioning (r = −.544) of the Short Form 36 Health Survey (SF-36). Similarly, construct validity of DASH-W also showed good correlation with the sub-domains of physical functioning (r = −.510) and bodily pain (r = −.503) of SF-36. Conclusion The Chinese (Queen Mary Hospital, Hong Kong version) Disabilities of the Arm, Shoulder and Hand is considered as a reliable and valid instrument that can provide a standardised measure of patient-centred outcomes for patients with upper extremity musculoskeletal disorders in Hong Kong.